Health inequalities and health-related economic inactivity: Why good work needs good health - Paul Crawshaw; Joanne Gray; Catherine Haighton; Scott Lloyd (Elsevier, 2024)
Tackling health inequalities demands whole systems strategies with reach beyond the traditional sphere of influence of health care systems. Practitioners and researchers have long recognised that wider social determinants, where people are born, the communities they live in, their built environment, access to education and resources and, most significantly for this discussion, their relationship to the labour market, profoundly shape health experiences and expectations over the lifecourse. At macro-level, economic structures and systems play a fundamental role in the distribution of good health and incidence of inequalities. Regionally, the health of local labour markets, a phenomenon shaped by macro, national and global economic forces, is a powerful determinant of opportunities to access and remain in work. Simultaneously, health status impacts significantly on ability to participate in paid employment. Absence from the labour market is both a cause and symptom of health inequalities.Economic inactivity, where people are both not participating in the labour market, or actively seeking or available for work, is strongly correlated with poor health. In the UK, over one third of the economically inactive experience long-term health problems. The implications for health inequalities, as both cause and symptom are clear. Participation in paid work, where appropriate, can be beneficial both economically and for health and wellbeing. Continued absence from the labour market is directly correlated with ill health. The determinants of health-related economic inactivity are complex and can only be understood using ecological models of public health. This presents significant challenges for politicians and policymakers alike concerned with reducing economic inactivity, delivering economic growth and redressing regional disparities.